Showcasing Nursing Leadership and Contributions to a University's COVID-19 Student Contact Tracing Process. Issue 4 (October 2021) - Jones, Pam; Walker, Jessica; Kleinpell, Ruth; George, Andrea; Norman, Linda
Abstract : The COVID-19 pandemic was an unprecedented event that impacted every segment of healthcare, including universities preparing healthcare professionals. Instituting processes to coordinate student return to campus and ongoing COVID-19 testing and contract tracing challenged university campuses, but also brought opportunities for collaboration. This article reports on the experiences of one nonprofit private higher education university in management of the COVID-19 testing and contact tracing that were led by school of nursing faculty and nursing leadership.